The effects of online learning towards students' stress levels during the covid-19 pandemic - Alven Dino Pandairoth; Rebekah Malik (Science Midwifery, 2023)
This study aims to determine the relationship between the influence of online learning and the student's stress level batch 2020 at the Faculty of Medicine, Tarumanagara University. The research methodology used an observational study with an analytic research design. Data collection was carried out by distributing questionnaires to 62 students batch 2020 at the Faculty of Medicine, Tarumanagara University. The research result showed that the effectiveness of online learning during the Covid-19 pandemic was comparable to those ineffective, as many as 31 respondents or each with a value of 50%. Students who experienced mild to moderate stress levels were 30 respondents, and students with moderate to severe stress levels were 32. Online learning that was carried out caused the increase in stress level in students. Thus, there is a relationship between online learning and students’ stress levels. However, the results of the effectiveness of online learning during the Covid-19 pandemic were comparable to those that were ineffective. This could happen because of the small number of respondents and the other factors that were not examined. Therefore, it is recommended for further research to analyze samples from all batches.